Method For Determining the Dynamics of Rodentia - Ешчанова Сайёра Шукурилла қизи; Елтаева Айгерим Азат кизи (Zien Journals, 2023)
This article presents information about the experience of artificial cultivation of Artemia in the Chimbai district of our republic and about research works on artificial cultivation of Artemia using intensive methods tested by scientists of the University of Canto, Vietnam
Keywords: Arthropoda; Crustacea; Brachiopoda